2019
DOI: 10.1093/jme/tjz073
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Synergistic Effect of Kairomones and Light-Emitting Diodes on the Attraction of Phlebotomine Sand Flies to Light Traps in Brazil

Abstract: The synergistic effect of light-emitting diodes (LEDs) and kairomones on the attraction of sand flies to light traps was evaluated. Octenol and lactic acid were used as chemical attractants. Green LEDs and the incandescent lamps were used as light attractants. Five CDC-type light traps with the respective combination of attractants (incandescent lamp, incandescent lamp + chemical attractant, green LED, green LED + chemical attractant, and chemical attractant alone [without light]) were set between 18:00 and 06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In fact, several researches demonstrate the effectiveness of light as an attractant both for Pyralidae ( Kanno et al 1985 , Loganathan et al 2001 , Sambaraju and Phillips 2008 ) and other Lepidoptera families like Crambidae ( Keszthelyi and Sáringer 2003 , Haihua et al 2016 ), and Hyblaeidae ( Loganathan et al 2001 ). Light traps are already widely used to capture Diptera like Chironomidae ( van Grunsven et al 2014 ), Culicidae ( Burkett et al 1998 , Silva et al 2019b ), Psychodidae Phlebotominae ( Cohnstaedt et al 2008 , da Silva et al 2019a ), and other 14 families ( Ndengué et al 2019 ). Moreover, this light trap has already been tested on other orders, like Diaphorina citri (Hemiptera: Liviidae) ( Mangan and Chapa 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several researches demonstrate the effectiveness of light as an attractant both for Pyralidae ( Kanno et al 1985 , Loganathan et al 2001 , Sambaraju and Phillips 2008 ) and other Lepidoptera families like Crambidae ( Keszthelyi and Sáringer 2003 , Haihua et al 2016 ), and Hyblaeidae ( Loganathan et al 2001 ). Light traps are already widely used to capture Diptera like Chironomidae ( van Grunsven et al 2014 ), Culicidae ( Burkett et al 1998 , Silva et al 2019b ), Psychodidae Phlebotominae ( Cohnstaedt et al 2008 , da Silva et al 2019a ), and other 14 families ( Ndengué et al 2019 ). Moreover, this light trap has already been tested on other orders, like Diaphorina citri (Hemiptera: Liviidae) ( Mangan and Chapa 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Light traps using incandescent bulbs generally catch fewer flies than light traps emitting UV (<400 nm) light [46][47][48][49][50][51][52]. However, LEDs can be both less attractive [9,15,17,49,[53][54][55][56][57] and more attractive [18,19,[58][59][60][61][62][63] than incandescent or fluorescent lights. In studies where LEDs have been found to be less attractive, the LED is usually white.…”
Section: Lighting Technologymentioning
confidence: 99%
“…Also D. melanogaster is most sensitive to short wavelength lights (ultraviolet, blue, and green) with two peaks at 420 nm and 495 nm ( de Salomon and Spatz 1983 , Kelber and Henze 2013 ). Light traps with similar wavelengths are largely used for moth monitoring, but they may also intercept Diptera ( Kim and Lee 2014a , da Silva et al 2019 , Ndengué et al 2019 , Silva et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%